O relacionamento franqueador franqueado e seus conflitos - Felipe Augusto Ferrarez Da Mata (2016)
This study aimed to present the dynamics of the franchisor-franchisee relationship and which are the most present conflicts of this relationship according to the franchisors IE Intercâmbio, Number One and Odontoclinic. Also we analyzed whether these conflicts can justify the adoption for the franchise business model by the companies surveyed. Three theoretical approaches (theory of resources scarcity, agency theory and institutional theory) were selected to explain this relationship, since its genesis, the need of the decision of the company by franchising process at the expense of organic growth, and also the relationship between franchisor -franchisee the contract signing process, operation start of the franchise and the day to day relationship. We also try to identify the most related conflicts in all these steps and how to give the resolution of this conflict. As methodology, this research used a qualitative approach using a multiple case study. Data collection occurred through semi-structured interviews and the analysis of data was performed using content analysis. This research was important for the theoretical study of the franchise, as it was considered whether the privileges used for adoption of the model franchises by the networks, would be able to sufficiently justify the existing conflicts in the franchisor-franchisee relationship.